Validation of quantitative RP-HPLC-DAD method and extraction optimization of 4-methoxycinnamyl p-coumarate and trans-4- methoxycinnamaldehyde in Etlingera pavieana rhizomes - Klaokwan Srisook&, Chartchai Malapong, Petchrat Sawai, Ekaruth Srisook& (Journal of Applied Pharmaceutical Science, 2021)
Etlingera pavieana is known as a spice and medicinal plant. According to previous reports, E. pavieana extracts exhibit various biological activities. However, the content of the primary phenylpropanoids of the E. pavieana rhizomal extract, 4-methoxycinnamyl p-coumarate (MCC) and trans-4-methoxycinnamaldehyde (MCD), has not been determined. This study was designed to validate a reversed-phase high-performance liquid chromatography method that quantified MCC and MCD from E. pavieana extracts. The method was validated based on the international council for harmonization (ICH) guidelines. The method displayed acceptable validation parameters, such as an excellent correlation coefficient higher than 0.999. The linearities of the response range of MCD and MCC were 1.00–20.00 and 2.5–60.00 µg/ml, respectively. The limit of detection and limit of quantitation were found to be 4.16 and 12.48 ng/ml, respectively, for MCD and 10.42 and 31.26 ng/ml, respectively, for MCC. The percentage relative standard deviation (RSD) of repeatability and intermediate precision were 1.03%–5.80% and 3.14%–6.84%, respectively. The ethyl acetate extracts prepared by the maceration and reflux method yielded the largest amount of MCD and MCC. This study confirmed that the high-performance liquid chromatography method for the simultaneous analysis of MCD and MCC was accurate, sensitive, and reproducible. This method can be used to quantitate the content of MCD and MCC in E. pavieana extracts.
Keywords: Etlingera pavieana, extraction solvent, HPLC, 4-methoxycinnamyl p-coumarate, trans-4- methoxycinnamaldehyde, validation